The use of folk physical training facilities during the realization of sporting holidays in preschool educational institutions - Smal, Yaroslav (Journal of Education, Health and Sport, 2016)
Smal Yaroslav. The use of folk physical training facilities during the realization of sporting holidays in preschool educational institutions. Journal of Education, Health and Sport. 2016;6(6):415-423. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55877 http://ojs.ukw.edu.pl/index.php/johs/article/view/3592 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. THE USE OF FOLK PHYSICAL TRAINING FACILITIES DURING THE REALIZATION OF SPORTING HOLIDAYS IN PRESCHOOL EDUCATIONAL INSTITUTIONS Yaroslav Smal Lesya Ukrainka Eastern European National University Key words: folk physical training, preschool educational institutions. Annotation The introduction of folk physical training facilities during the realization of sporting holidays is actual for a future revival, children’s awareness of their nation values, their understanding of the importance of folk physical training facilities. Sporting holidays: calendar, folklore, ceremonial, the days of name-days celebrations are held according to a Christian calendar (Christmas, Maslyana, Easter, Trinity). They are formed on accessible to children material with the use of folk mobile games, funs, folk round dances, songs, attributes of national clothes, appliances. The use of folk physical training facilities during the realization of sporting holidays will enable not only to increase the efficiency of physical health-improving process but also will have a positive influence on the state of health and motive preparedness of senior children under school age, and also will form their interest to the systematic physical training lessons.